Pandemic, Climate Mitigation, and Reshoring : Impacts of a Changing Global Economy on Trade, Incomes, and Poverty - Chepeliev, Maksym; Maliszewska, Maryla; Osorio-Rodarte, Israel; Seara E Pereira, Maria Filipa; Van Der Mensbrugghe, Dominique (Washington, DC: World Bank, 2022)
The resilience of global value chains has been put to the test by the COVID-19 pandemic, extreme weather events, and trade tensions spurred by growing economic nationalism and protectionism. Shocks in production and trade can be transmitted from one country to another by global value chains, although they can also help to lessen the blow of a domestic shock, such as a lockdown, and drive economic recovery. What shocks to global value chains should be anticipated in the coming years Is it possible to design policies that can enhance resilience to trade shocks in developing countries without endangering growth This paper explores simulations from the ENVISAGE global computable general equilibrium model to enhance understanding of the potential longer-term impacts of COVID-19 and the policy responses it engenders in developing countries. The paper assesses the likely impacts of measures designed to reshore production and reduce reliance on imports. It also evaluates other key factors shaping the global economy, including stylized scenarios to capture the essential elements of policies to achieve carbon emission reductions that will have an impact on trade.